Realization of business rules represented using formal logic sentences in information systems - Lebedys, Evaldas; Vasilecas, Olegas (Lietuvos matematikos rinkinys, 2004)
The paper deals with the problems of creating business rules model that would be formal enough for automated transformation to Information systems model and realization in program systems. There are many modelling languages and diagrams suitable to model business rules of different classes, but there is no one ideal. Every modeling language used to model business rules has to be formal enough and understandable for business people with no additional knowledge. The choice of modelling language may impact completeness, understandability and the level of formalization. This may also impact the process of transformation of created model to Information systems model. In this work it is proposed to model business rules using formal logic sentences.
Keywords: business rule model; business rule representation; formal logic